Variation in secondary metabolite production as well as antioxidant and antibacterial activities of Zingiber zerumbet (L.) at different stages of growth - Ghasemzadeh, Ali; E. Jaafar, Hawa Z.; Ashkani, Sadegh; Rahmat, Asmah; Juraimi, Abdul Shukor; Puteh, Adam; Tengku Muda Mohamed, Mahmud (BioMed Central, 2016)
Background:Zingiber zerumbet (L.) is a traditional Malaysian folk remedy that contains several interesting bioactive compounds of pharmaceutical quality.